Новая ротационная гипотеза структурообразования и металлогения - Тяпкин, К.Ф. (Видавничий дім "Академперіодика" НАН України, 2007)
Some tectonical aspects of a new rotational hypothesis on the structure formation, the nature of the tectonical activization of the Earth, and the mechanism of formation of geosynclines on the basis of deep-seated faults are exposed. The necessity and possibility of applying these conceptions in modern metallogeny is discussed.